Screening for colorectal cancer: reasons for refusal of faecal occult blood testing in a general practice in England. Issue 1 (February 1995) - Hynam, K A; Hart, A R; Gay, S P; Inglis, A; Wicks, A C; Mayberry, J F
Abstract : STUDY OBJECTIVE–To ascertain reasons for non-compliance with faecal occult blood tests in colorectal cancer screening programmes. DESIGN–A standard interview by a trained nurse of a random sample of those who declined screening. SETTING–The Leicestershire town of Market Harborough, where most of the 25, 000 population are served by a single general practice of 10 partners. PARTICIPANTS–Altogether 4185 residents aged 51 to 70 years were invited to receive a free faecal occult blood test (Haemoccult). Eighty one subjects from a sample of 351 who wrote declining the offer were interviewed. MAIN RESULTS–Non-compliers were divided into those who did not request a test kit and those who returned an unused kit. In the former group the commonest reasons given were intercurrent illness (39%), fear of further tests and surgery (24%), and feeling well (22%). For those who returned unused kits the commonest reasons were the unpleasantness of the stool collection procedure (65%), feeling well (30%), intercurrent illness (23%), and fear of further tests and surgery (20%). In both groups the main concern of those who did not comply were fear of further diagnostic tests and surgery rather than concern at the lack of effective treatment for cancer. CONCLUSIONS–To increase compliance, education and publicity must explain the concept of asymptomatic illness and allay people's fear of hospital investigation and treatment. The benefits of screening should be particularly emphasised to those who return kits so they may overcome their reservations.